SYNTHESIS AND BIOLOGICAL EVALUATION OF SOME NEW 10-[(3-SUBSTITUTEDAMINO) 1, 2, 4- DITHIAZOLO] 2-CHLOROPHENOTHIAZINES - B. R. Deshmukh; R. D. Isankar (The Bioscan, 2024)
In recent times, a series of 10-[(3-substitutedamino) 1, 2, 4- dithiazolo] 2-chlorophenothiazines was synthesized by the oxidative cyclization with liquid bromine in chloroform medium by conventional method. This method has broad applications due to the efficacy of this approach makes it suitable for accelerating a variety of organic processes, resulting in increased yield, improved selectivity, and reduced production of by-products. As a result, this approach provides a simpler process for extracting the desired products, which are produced in a relatively pure state. Synthesized compounds are verified by elemental analysis, chemical characterization and spectral analysis like IR, NMR and Mass. All synthesized compounds (4a-d) showed moderate-to-significant anti-bacterial and anti-fungal activity. Compound 4d showed moderate activity against breast carcinoma (MCF-7) cell lines with IC50 values of 49.52 μM.